Evaluasi Implementasi Kedisiplinan dan Tatatertib Siswa MI Nurul Khalifah Bima Sape - Sahrul; Suaeb; Anhar; Samsudin (Universitas Ngudi Waluyo, 2023)
The aim of the research is to know the level of discipline and discipline of students. The subjects in this study were MI Nurul Khalifah Bima Sape students. This research is a descriptive qualitative research. The results of the interview with the school principal (Arifin Hamzah, S.H) on October 23, 2022 at 09.30 WITA students always arrive at school on time, wear school uniforms, attend flag ceremonies every Monday, and so on. There are several causative factors that become obstacles to discipline and student discipline related to MI Nurul Khalifah Bima, unexpected obstacles, for example a car tire bursting on the road so that it becomes the cause of the problem, besides that the awareness of students and school residents is still low. The research data were obtained qualitatively and quantitatively using observation, interviews, document study, and questionnaires. The results of the study showed that students were already in the school environment before starting time, students attended the ceremony every Monday, before the lesson began students always prayed, students were not noisy in class, students actively discussed during learning, did not disturb friends while studying, students obeyed the rules issued by the school. The results of the data analysis show that the level of student discipline is 90% while in student discipline it is 89% so that the level of discipline and order of students at MI Nurul Khalifah Bima Sape is in the very good category. Tujuan penelitian dapat mengetahui tingkat kedisiplinan dan tatatertib siswa. Subyek dalam penelitian ini siswa MI Nurul Khalifah Bima Sape. Penelitian ini merupakan penelitian kualitatif deskriptif. Hasil wawancara bersama kepala sekolah (Arifin Hamzah, S.H) pada tanggal 23 Oktoebr 2022 pukul 09.30 Wita siswa ketika datang kesekolah selalu tepat waktu, memakai pakaian seragam sekolah, mengikuti upacar bendera setiap hari senin, dan lain sebagainya. Ada beberapa faktor penyebap yang menjadi kendala kedisiplinan dan tata tertib siswa terkait dengan MI Nurul Khalifah Bima kendala yang tak terduga misalnya ban mobil pecah di jalan sehingga menjadi penyebab dari kendalanya, selain itu kesadaran peserta didik dan warga sekolah masih rendah. Data penelitian diperoleh kualitatif dan kuantitatif menggunakan observasi, wawancara, studi dokumen, kuesioner. Hasil penelitian bahwa siswa sebelum jam masuk siswa sudah berada di lingkungan kesekolah, siswa mengikuti upacara setiap hari senin, sebelum pelajaran dimuali siswa selalu berdoa, siswa tidak ribut didalam kelas, siswa aktif berdiskusi saat pembelajaran berlangsung, tidak mengganggu teman saat belajar, siswa mematuhi aturan yang sudah dikeluarkan oleh sekolah. Hasil analisis data bahwa tingkat kedisiplinan siswa terdapat 90% sedangkan pada tata tertib siswa sebesar 89% sehingga tingkat kedisplinan dan tata tertib siswa MI Nurul Khalifah Bima Sape berada pada kategori sangat baik.